Document analysis systems : 14th IAPR International Workshop, DAS 2020, Wuhan, China, July 26-29, 2020, Proceedings /: 14th IAPR International Workshop, DAS 2020, Wuhan, China, July 26-29, 2020, Proceedings. (2020) - Unknown
No abstract available